Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1097/wnf.0000000000000292
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Effectiveness of Fingolimod in Real-World Multiple Sclerosis Portuguese Patients

Abstract: In this real-world audit, fingolimod appeared to be effective after first-line treatment failure in reducing disease activity and progression of disability throughout the observational period and may be an effective option after natalizumab. Fingolimod was well tolerated with low rates of discontinuation and adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
6
3
0
Order By: Relevance
“…These results are in accordance with those reported by the PANGAEA study after 5 years of fingolimod therapy [22], a study conducted with similar methodological characteristics as the current study [23]. These results are also consistent with previously reported Portuguese studies whose results also showed a decrease in ARR in the first year of treatment with fingolimod [11,18] and with the MS NEXT study that reported a 76% decrease in ARR after 2 years of fingolimod [20].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…These results are in accordance with those reported by the PANGAEA study after 5 years of fingolimod therapy [22], a study conducted with similar methodological characteristics as the current study [23]. These results are also consistent with previously reported Portuguese studies whose results also showed a decrease in ARR in the first year of treatment with fingolimod [11,18] and with the MS NEXT study that reported a 76% decrease in ARR after 2 years of fingolimod [20].…”
Section: Discussionsupporting
confidence: 93%
“…However, in this last study, the percentage of relapse-free patients decreased from years 1 to 3 of fingolimod treatment. Nevertheless, the percentage of patients with no relapses during the 3 years of fingolimod treatment was 60.8% [18], similar to that observed in our study.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations